Improvement in the performance of two layered model pavement with treated coir geotextile at the interface. (5th July 2022) - Jaswal, Priya; Vivek,; Sinha, SK
The primary objective of this research work is to study the effect of surface treated coir geotextiles on the bearing behaviour of sand overlying clay model with geotextiles at the interface. Two woven and two non woven coir geotextiles were treated with bitumen emulsion and unsaturated polyester resin. The surface morphology and thermal stability were investigated by scanning electron micrograph and simultaneous thermal analyser respectively. The bearing ratio of sand overlying clay increased with treated woven/non woven coir geotextiles at the interface in soaked and unsoaked condition. The bearing ratio was higher for treated/untreated and woven/non woven coir geotextiles at the interface in unsoaked condition as compared to soaked condition. The chemical treatment improved the thermal stability of surface treated coir geotextiles through physical and chemical changes.